KINERJA SUB DAERAH ALIRAN SUNGAI PALUH BESAR BERDASARKAN ASPEK KELESTARIAN LINGKUNGAN ( Performance of Paluh Besar Sub Watershed Based on Aspects of the Environmental Sustainability) - Maroloan Sitanggang; Sumono Sumono; Sulastri Panggabean (Jurnal Rekayasa Pangan dan Pertanian, 2018)
ABSTRACT Paluh Besar Sub Watershed is one of the Sub Watershed of the Watershed Deli located at the downstream and has an area of 10880 hectares. Paluh Besar Sub Watershed is highly vulnerable to flooding because it is an utilization area with a slope of less than 8%. This study was aimed to determine the performance of the subzone Paluh based on aspects of environmental sustainability. The parameters analyzed were the percentage of critical land, the percentage of vegetation cover, erosion index, the coefficient of the flow regime, the annual flow coefficient, sediment load, flood frequency, water usage index, protected areas and cultivation area. From this study, the percentage values obtained were: critical land was 20.63% (very high grade), the percentage of vegetation cover was 53.81% (medium grade), the erosion index was 0.089 (very low grade), the flow regime coefficient was 2.46 (low grade), the annual flow coefficient was 0.39 (medium grade), sediment load was 0.25 (very low grade), frequency of floods was more than once a year (very high grade), water usage index was 5.23  (medium grade), protected areas was 0 (very poor grade), cultivated area was 100% (very low grade). Based on these results the carrying capacity of the river basin of subzone Paluh Besar was classified (based on aspects of environmental sustainability) in the medium class with a total score of 71.5. Keywords: Paluh    Besar    Sub    Watershed,    performance,    aspects   of   environmental sustainability. ABSTRAK Sub DAS Paluh Besar adalah salah satu Sub DAS dari DAS Deli yang terletak dibagian hilir dan mempunyai luas sebesar 10.880 Ha. Sub DAS Paluh Besar sangat rentan terhadap masalah banjir karena merupakan daerah pemanfaatan dengan kemiringan lereng kurang dari 8%. Penelitian ini bertujuan untuk mengetahui kinerja Sub DAS Paluh Besar berdasarkan aspek kelestarian lingkungan. Parameter yang dianalisis adalah persentase lahan kritis, persentase penutupan vegetasi, indeks erosi, koefisien regim aliran, koefisien aliran tahunan, muatan sedimen, frekuensi banjir, indeks penggunaan air, kawasan lindung dan kawasan budidaya. Dari penelitian ini diperoleh nilai persentase lahan kritis sebesar 20,63% termasuk kelas sangat tinggi, persentase penutupan vegetasi sebesar 53,81% termasuk kelas sedang, indeks erosi sebesar 0,089 termasuk kelas sangat rendah, koefisien regim aliran sebesar 2,46 termasuk kelas rendah, koefisien aliran tahunan sebesar 0,39 termasuk kelas sedang, muatan sedimen sebesar 0,25 termasuk kelas sangat rendah, frekuensi banjir lebih dari sekali dalam setahun termasuk kedalam kelas sangat tinggi, indeks penggunaan air sebesar 5,23 termasuk kedalam kelas sedang, kawasan lindung sebesar 0 termasuk kedalam kelas sangat buruk, kawasan budidaya sebesar 100% termasuk kedalam kelas sangat rendah. Berdasarkan hasil ini daya dukung DAS Sub DAS Paluh Besar berdasarkan aspek kelestarian lingkungan diklasifikasikan dalam kelas sedang dengan total skor sebesar 71,5. Kata kunci : Sub DAS Paluh Besar, kinerja, aspek kelestarian lingkungan.